Evaluation of Oxidative Stress In Patients With Giardia Lamblia In Duhok City, Iraq - Ismail H. Slevaney; Muna H. Jankeer; Senaa Abdullah Ali .Al-Jarjari (South Eastern European Journal of Public Health, 2024)
Giardia lamblia (Giardia intestinalis) is a widespread enteric parasite known as giardiasis, which infects the small intestine of human at different ages, particularly children. This parasite has direct and indirect effects on the host’s body. This study aimed to evaluate the role of oxidative stress is expressed by estimating the malondialdehyde concentration (As oxidative indicator), and estimating the non-enzymatic antioxidants concentration in the serum of 39 patients ( males and females), whose ages ranged between (3-38) years patients infected with the G.lamblia or suspected of being infected with this parasite who were referred to Public Health Prevention Center, Center, Heevi Pediatric Hospital, Shariya and Kaberto Camp inside or outside Dohuk city. The diagnosis of parasitic infection was confirmed on the clinical symptoms of patients, the macroscopic examination of stool infected patients, which cotained trophozoites and / or cysts of G. lamblia, by confirming the infection microscopically in the laboratory by two method the direct wet smear examination and the antigen detection test. in addition to 30 serum samples healthy controls who did not have this disease, of both genders and the same age as a healthy control.The results of current study showed a significant increase in the malondialdehyde (MDA) concentration by 158% in the serum of patients with giardiasis compared to healthy controls of both genders, and by 183% in males, 134% in females. compared to healthy controls according to gender. And the results also showed a significant decrease in the concentration of both glutathione (GSH) and albumin in the serum of infected patients by 70% and 15%, respectively, compared to healthy controls of both genders. The significant percentage of decrease was in males by 71%, 16% respectively, and in females by 70% and 14% respectively compared with healthy controls according to gender. We conclude that infection with G. lamblia caused oxidative stress and dysfunction in physiological and metabolic processes.